2021
DOI: 10.1186/s13046-021-01871-4
|View full text |Cite
|
Sign up to set email alerts
|

RBM15 facilitates laryngeal squamous cell carcinoma progression by regulating TMBIM6 stability through IGF2BP3 dependent

Abstract: Background Laryngeal cancer has the highest mortality rate among head and neck tumours. RNA N6-methyladenosine (m6A) is the most plentiful and variable in mammalian mRNA. Yet, the m6A regulatory mechanism underlying the carcinogenesis or progression of LSCC remains poorly understood. Methods The m6A RNA methylation quantification kit was used to detect tissue methylation levels. m6A microarray analysis, mRNA transcriptomic sequencing (mRNA-seq), an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
108
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 39 publications
(23 reference statements)
7
108
0
Order By: Relevance
“…Our study indicated that high expression of VIRMA, METTL14, and RBM15B, and low expression of EIF3B, YTHDF1, and YTHDF3 is correlated with longer OS, and these genes could serve as markers to predict the prognosis of BIC (Figure 4). There are common and unique genes in the final set of identified genes as prognostic markers in our and the other cancer studies [63,75,79] which highlight the diverse roles of the m 6 A pathway genes in the progression of different human malignancies. To get more insights into the underlying mechanisms, the association of mutation frequency of the genes with prognostic value was examined and nine of the m 6 A pathway genes (METTL14, RBM15, WTAP, HNRNPA2B1, SRSF2, YTHDF1, YTHDF2, YTHDF3, and ALKBH5) were correlated with the prognosis of BIC (Figure S4).…”
Section: Discussionmentioning
confidence: 73%
“…Our study indicated that high expression of VIRMA, METTL14, and RBM15B, and low expression of EIF3B, YTHDF1, and YTHDF3 is correlated with longer OS, and these genes could serve as markers to predict the prognosis of BIC (Figure 4). There are common and unique genes in the final set of identified genes as prognostic markers in our and the other cancer studies [63,75,79] which highlight the diverse roles of the m 6 A pathway genes in the progression of different human malignancies. To get more insights into the underlying mechanisms, the association of mutation frequency of the genes with prognostic value was examined and nine of the m 6 A pathway genes (METTL14, RBM15, WTAP, HNRNPA2B1, SRSF2, YTHDF1, YTHDF2, YTHDF3, and ALKBH5) were correlated with the prognosis of BIC (Figure S4).…”
Section: Discussionmentioning
confidence: 73%
“…Accumulating data indicates the significant role of m 6 A RNA modification in the post-transcriptional regulation of gene expression that determines the proper function of crucial physiological processes. Therefore, disturbances in m 6 A RNA methylation may lead to the development of pathological changes, including cancers [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. HNSCC initiation, progression, and growth are complex molecular processes encompassing genetic and epigenetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pancreatic cancer, the higher level of m 6 A modification measured using HPLC/MS was also correlated with patients’ overall survival and with more lymphatic metastases [ 22 ]. Among head and neck cancers, the higher level of m 6 A RNA modification in tumor tissues was found in 34 laryngeal squamous cell carcinoma (LSCC) and paired-matched adjacent normal tissues [ 14 ]. However, the measurements were done with a colorimetric method that is less sensitive than LC-ESI-MS/MS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M6A modi cation is mainly mediated by the m6A methyltransferases, demethylases and reader proteins. The m6A methyltransferases mainly included methyltransferase-like 3 (METTL3) [4], methyltransferaselike 14 (METTL14) [5], and Wilms tumor 1 associated protein (WTAP) [6], RNA binding motif protein 15 [7], and vir like m6A methyltransferase associated [8]. The m6A demethylases mainly included fat-mass and obesity-associated protein (FTO) [9], alkylation repair homolog protein 5 (ALKBH5) [10].…”
Section: Introductionmentioning
confidence: 99%